Acute Down-regulation of BDNF Signaling Does Not Replicate Exacerbated Amyloid-β Levels and Cognitive Impairment Induced by Cholinergic Basal Forebrain Lesion - Turnbull, Marion T.; Boskovic, Zoran; Coulson, Elizabeth J. (Frontiers in Molecular Neuroscience, 2018)
Degeneration of basal forebrain cholinergic neurons (BFCNs) precedes hippocampal degeneration and pathological amyloid-beta (Aβ accumulation and underpins the development of cognitive dysfunction in sporadic Alzheimer’s disease (AD). We hypothesized that degeneration of BFCNs causes a decrease in neurotrophin levels in innervated brain areas, which in turn promotes the development of Aβ pathology and cognitive impairment. Here we show that lesion of septo-hippocampal BFCNs in a pre-symptomatic transgenic amyloid AD mouse model (APP/PS1 mice) increases soluble Aβ levels in the hippocampus, and induces cognitive deficits in a spatial memory task that are not seen in either unlesioned APP/PS1 or wildtype littermate control mice. Furthermore, the BFCN lesions result in decreased levels of brain-derived neurotrophic factor (BDNF). However, viral knockdown of neuronal BDNF in the hippocampus of APP/PS1 mice (in the absence of BFCN loss) neither increased the levels of Aβ nor caused cognitive deficits. These results suggest that the cognitive decline and Aβ pathology induced by BFCN loss occur independent of dysfunctional neuronal BDNF signaling, and may therefore be directly underpinned by reduced cholinergic neurotransmission.